Menavigasi Transisi ITB Innovation Park melalui Perspektif Multi Tingkat - Afrianto, Adi; Astari, Rahmita; Netra, Putri Aulia; Arisanti, Mariata; Yuliar, Sonny (Jurnal Sosioteknologi, 2025)
The development of the science techno park (STP) in Indonesia aims to facilitate innovation-based industrial growth. Concurrently, the Bandung Institute of Technology (ITB) is committed to realizing an entrepreneurial university by leveraging research results through the ITB-STP, also known as the ITB Innovation Park (IIP). The IIP acts as an innovation center that connects research with market needs and functions as an innovation commercialization accelerator. Research using the Multi-Level Perspective Framework indicates policy shifts in STP development during the 2015– 2019 and 2020–2024 periods. Despite producing various innovative products, IIP faces challenges in transitioning the socio-technical system for commercializing research outputs, particularly in integrating with the broader regime and ensuring innovation sustainability. IIP’s initiatives demonstrate instances of fit & fit; however, during the fit & stretch phase, IIP continues to encounter challenges, particularly concerning market responses to the innovative products offered. This indicates that the stretching process remains in progress. Consequently, IIP’s success in reshaping the regime depends on enhanced collaboration, systematic innovation validation, and supportive government policies to foster the establishment of a new innovation-based regime.